2017
DOI: 10.1104/pp.17.01370
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Host Factor Required for Antiviral RNAi and Amplification of Viral siRNAs

Abstract: Small interfering RNAs (siRNAs) are processed from virus-specific dsRNA to direct antiviral RNA interference (RNAi) in diverse eukaryotic hosts. We have recently performed a sensitized genetic screen in Arabidopsis () and identified two related phospholipid flippases required for antiviral RNAi and the amplification of virus-derived siRNAs by plant RNA-dependent RNA polymerase1 (RDR1) and RDR6. Here we report the identification and cloning of - () from the same genetic screen. encodes a multispan transmembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Transcriptome and RT-qPCR analyses revealed that CMV infection induced the expression of a number of R genes ( Figure 5 ), as well as SA biosynthesis and signaling ( Figure 7 ), which required the presence of the 2b protein, consistent with recent reports that CMV infection induced host factors with antiviral effects and these effects relied on the function of 2b [ 47 , 48 ]. Although only a few of these genes were found to be related to the direct effect of 2b-mediated demethylation on their induction ( Figure 3 C), a large amount of 2b-dependent Hypo-DMR loci detected in CMV infection would also imply a defensive effect ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 86%
“…Transcriptome and RT-qPCR analyses revealed that CMV infection induced the expression of a number of R genes ( Figure 5 ), as well as SA biosynthesis and signaling ( Figure 7 ), which required the presence of the 2b protein, consistent with recent reports that CMV infection induced host factors with antiviral effects and these effects relied on the function of 2b [ 47 , 48 ]. Although only a few of these genes were found to be related to the direct effect of 2b-mediated demethylation on their induction ( Figure 3 C), a large amount of 2b-dependent Hypo-DMR loci detected in CMV infection would also imply a defensive effect ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 86%
“…GUS staining assays were performed as described previously ( Guo et al , 2018 ). Briefly, plant tissues were treated with X-Gluc solution (3 mM 5-bromo-4-chloro-3-indolyl-β- d -glucuronide, 10 mM potassium ferricyanide, 0.1% Triton X-100, 10 mM potassium ferrocyanide, 50 mM NaH 2 PO 4 buffer, pH 7.0) at 37 °C overnight, washed in an ethanol series, and photographed using a digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, AGO1 association to a membrane compartment, through a yet unknown mechanism that depends on the mevalonate (MVA)-isoprenoid pathway, is required to sustain a functional RNA silencing activity (Brodersen et al, 2012). Host factors presumably participating in the formation of membrane-bound compartments and specifically involved in antiviral RNA silencing have been recently identified (Guo et al, 2017;Guo et al, 2018;Zhu et al, 2017). Viral RNA silencing suppressor (RSS) proteins aim to arrest the silencing mechanism to protect the viral genome from degradation (Csorba, Kontra, & Burgyán, 2015;Nakahara & Masuta, 2014).…”
Section: Wilkinsmentioning
confidence: 99%
“…Moreover, AGO1 association to a membrane compartment, through a yet unknown mechanism that depends on the mevalonate (MVA)‐isoprenoid pathway, is required to sustain a functional RNA silencing activity (Brodersen et al, ). Host factors presumably participating in the formation of membrane‐bound compartments and specifically involved in antiviral RNA silencing have been recently identified (Guo et al, ; Guo et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%